MODERATING EFFECT OF WORK EXPERIENCE IN THE INFLUENCE OF PROFESSIONALISM, INDEPENDENCE, AND COMPETENCE ON AUDIT QUALITY - Poernamawatie, Fahmi; Hidayah, Wahyuni; Widyawati , Titis Indah; Siagian, Deriska Emiria; Hertanto, Ronny Hendra (JURNAL EKBIS, 2025)
The issue of declining audit quality in Indonesia has now become a public concern. The number of cases involving public accountants in financial scandals can have a major impact on both the economy, public trust, and the reputation of the accounting profession. This study aims to analyze the moderating effect of work experience on the effect of professionalism, independence, and competence on audit quality. Data were collected through a survey involving 42 KAP auditors in the Greater Malang area. Hypothesis testing was carried out using the PLS-SEM method. The results showed that professionalism had no significant effect on audit quality with a p-value of 0.220, independence and competence had a positive and significant effect on audit quality with a p-value of 0.047 and 0.083, respectively. Work experience is able to moderate the effect of professionalism on audit quality with a p-value of 0.086, but is unable to moderate the effect of independence and competence on audit quality with a p-value of 0.950 and 0.417. This finding indicates that although work experience can increase the impact of professionalism on audit quality, independence and competence factors still require continuous development that does not only rely on experience.